Effect of carbohydrate restriction on body weight in overweight and obese adults: a systematic review and dose–response meta-analysis of 110 randomized controlled trials - Soltani, Sepideh; Jayedi, Ahmad; Abdollahi, Shima; Vasmehjani, Azam Ahmadi; Meshkini, Fatemeh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2023)
Introduction Carbohydrate-restricted diets are one of the most effective dietary interventions for weight loss. However, the optimum carbohydrate intake for implementing the most effective weight-loss interventions is still being discussed. We aimed to determine the optimum carbohydrate intake for short- and long-term weight loss in adults with overweight and obesity. Methods We searched PubMed, Scopus, Web of Science, and CENTRAL from inception to May 2021 for randomized controlled trials examining the effect of a carbohydrate-restricted diet (≤45% of energy intake) as compared to a control diet (carbohydrate intake >45% of energy intake) on body weight in adults with overweight/obesity. A random-effects dose–response meta-analysis was conducted to calculate the mean difference for each 10% decrease in carbohydrate intake at the 6-month follow-up (1 to 6 months), 12-month follow-up (6 to 12 months), and follow-up longer than 12 months. The shape of the dose-dependent effects was also evaluated. The certainty of the evidence was rated using the GRADE approach. The minimal clinically important difference (MCID) threshold was defined as 5% weight loss (equal to 4.39 kg). Results A total of 110 trials were selected for the present meta-analysis. In the linear dose–response meta-analysis, each 10% decrease in carbohydrate intake reduced body weight by 0.64 kg (95% CI: −0.79 to −0.49; n = 101 trials with 4,135 participants, high-certainty evidence) at the 6-month follow-up and by 1.15 kg (95% CI: −1.61 to −0.69; 42 trials with 2,657 participants, moderate-certainty evidence) at the 12-month follow-up. Non-linear dose–response meta-analyses indicated a monotonic reduction in body weight with the decrease in carbohydrate intake, with the greatest reduction at 5% at the 6-month follow-up (mean difference 5%: −3.96 kg, 95% CI: −4.92 to −3.00) and 10% at the 12-month follow-up (mean difference 10%: −6.26 kg, 95% CI: −10.42 to −2.10). At follow-up longer than 12 months, dose–response analyses suggested a non-linear effect, wherein carbohydrate intakes higher than 40% and lower than 30% were not effective for weight loss. Discussion Carbohydrate restriction is an effective dietary strategy for important weight loss in adults with overweight and obesity. At 6-month and 12-month follow-ups, body weight decreased proportionally, more than the MCID threshold, along with the decrease in carbohydrate intake. At follow-up longer than 12 months, there was a non-linear effect, with the greatest reduction at 30% carbohydrate intake. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022315042.